Profiles of Coronary Artery Disease Patients Treated in a Tertiary Care Hospital of Bangladesh (University Heart Journal, 2026)
Background: Coronary artery disease (CAD) is a leading cause of morbidity and mortality in Bangladesh. Rapid urbanization, sedentary lifestyles, and rising cardiovascular risk factors have increased disease burden. Profiling patients in tertiary hospitals helps understand patterns and guide effective prevention and management strategies. Objective: To describe the sociodemographic features, risk factors, clinical presentation, and treatment patterns of coronary artery disease patients in a tertiary care hospital of Bangladesh. Methods: This prospective cross-sectional study was conducted at the Department of Cardiology, Bangladesh Medical University, Dhaka, Bangladesh, from January 2023 to December 2024. A total of 83 patients with confirmed CAD were enrolled using a purposive sampling technique. Data regarding demographic variables, risk factors, clinical manifestations, and management approaches were collected and analyzed using MS Office tools. Results: The mean age was 56.8 ± 9.7 years, with 72.3% males. Hypertension (65.1%), dyslipidemia (57.8%), diabetes mellitus (48.2%), smoking (44.6%), and family history (31.3%) were common. Typical chest pain occurred in 78.3%. ST elevation myocardial infarction, non-ST elevation acute coronary syndrome, and stable angina were observed in 38.6%, 33.7%, and 27.7%, respectively. Medical therapy, percutaneous coronary intervention, and coronary artery bypass grafting were used in 61.4%, 26.5%, and 12.1% of patients. Conclusion: Patients with coronary artery disease treated at this tertiary care hospital were predominantly middle-aged males with a high burden of modifiable risk factors. Strengthening preventive strategies and early risk factor control is crucial to reducing the impact of CAD in Bangladesh.University Heart Journal 2026; 22(1): 10-14